Reflecting the Role of International Organizations through WFP’s Food Aid Intervention in the Ethiopian Crisis (2019–2022) - Sandy Putra Aryanto; Januari Pratama Nurratri Trisnaningtyas (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
World Food Programme (WFP) is an international organization engaged in humanitarian work by providing food assistance to countries experiencing a food crisis. One of the countries currently receiving assistance from WFP is Ethiopia. Ethiopia is one of the countries experiencing a food crisis due to internal conflict, extreme climate change, natural disasters and the Covid-19 pandemic. Seeing the condition of Ethiopia experiencing a food crisis, WFP is present in Ethiopia to help overcome the food crisis. The purpose of this study is to determine how WFP's role through food assistance programs can overcome the food crisis in Ethiopia, especially during the pandemic. This study uses a qualitative method, researchers collect data from various sources such as books, journals, online news, the WFP website and other sources. This study uses the Theory of the Role of International Organizations in analyzing case studies. The results of the study show that WFP has succeeded in carrying out four roles as an international organization, namely as a problem solver, collective act mechanism, aid provider and capacity builder